Chinese minimally invasive percutaneous nephrolithotomy for intrarenal stones in patients with solitary kidney: a single-center experience. - Zhichao Huang; Fajun Fu; Zhaohui Zhong; Lei Zhang; Ran Xu; Xiaokun Zhao (PLoS ONE, 2012)
OBJECTIVE: To report our experience with Chinese minimally invasive percutaneous nephrolithotomy (Chinese MPCNL) to manage patients with intrarenal stones in solitary kidney, and evaluate the safety, efficiency and feasibility of this technique. METHODS: Forty-one patients with intrarenal stones in solitary kidney underwent Chinese MPCNL in our department from March 2009 to February 2011. Demographic characteristics, operative parameters, number of tracts, stone-free rates (SFRs), stone analyses, hemoglobin levels, nephrostomy tube removal time, hospitalization time, and complications were evaluated. Serum creatinine (Scr) and glomerular filtration rate (GFR) were measured preoperatively, postoperatively at 1 month, and each follow-up visit. The 5-stage classification of chronic kidney disease (CKD) was used according to the National Kidney Foundation guidelines. RESULTS: The initial stone-free status was achieved in 35 (85.4%) patients after Chinese MPCNL. The mean follow-up time was 16.9 ± 4.7 months (range: 12-24), and the final SFR improved to 97.6% after auxiliary procedures. Among all patients, complex stones were detected in 26 (63.4%) patients, and 9 (22.0%) required multiple tracts. The mean operative time and mean hospitalization time were 71.3 ± 23.5 min (range: 40-139) and 6.1 ± 0.5 days (range: 5-11), respectively. During preoperative period and postoperative period (1 month), Scr were 132.1 ± 41.3 umol/L (range: 78.2-231.4) and 108.9 ± 30.7 umol/L (range: 71.6-136.9), respectively (P<0.05), while GFR were 74.9 ± 24.2 ml/min (range: 35-110) and 83.9 ± 27.4 ml/min (range: 65-110), respectively (P<0.05). According to CKD classification, the renal function was stable, improved, and worse in 29 (70.7%), 11 (26.8%), and 1 (2.5%) patients, compared with the preoperative levels. No patient progressed to end-stage renal disease requiring dialysis. CONCLUSIONS: Our experience with Chinese MPCNL demonstrates that it is safe, feasible and efficient for managing the intrarenal calculi in solitary kidney with a low complication rate. At long-term follow-up, renal function stabilized or even improved in the majority of patients with solitary kidney.